Factors influencing customer intention to purchase automobile in Hanoi = Các nhân tố ảnh hưởng đến ý định mua ô tô của khách hàng tại Hà Nội - Đinh, Hoàng An (2020)
Content: This research focuses on customer intention to purchase automobile in Hanoi, a capital of Vietnam. By determining the factors and measuring the influences of factors on customer intention to purchase auto, the study will help other researchers and business practitioners in automobile industry in Vietnam to provide certain marketing programs to foster sale revenues and volume respectively. Location: This research is carried out in Hanoi, Vietnam. The survey of questionnaire is developed and then it is delivered to the customers who have been intention to purchase automobile in three automobile dealers of Toyota, Honda, and General Motors.